Panchromatic "Dye-Doped" Polymer Solar Cells: From Femtosecond Energy Relays to Enhanced Photo-Response - Grancini, G; Kumar, R; Maiuri, M; Fang, J; Huck, W; Alcocer, M; Lanzani, G; Cerullo, G; Petrozza, A; Snaith, H (2013)
There has been phenomenal effort synthesizing new low-band gap polymer hole-conductors which absorb into the near-infrared (NIR), leading to >10% efficient all-organic solar cells. However, organic light absorbers have relatively narrow bandwidths, making it challenging to obtain panchromatic absorption in a single organic semiconductor. Here, we demonstrate that (poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b0]dithiophene)-alt-4, 7-(2,1,3-benzothiadia-zole)] (PCPDTBT) can be "photo-sensitized" across the whole visible spectrum by "doping" with a visible absorbing dye, the (2,2,7,7-tetrakis(3-hexyl-5-(7-(4-hexylthiophen-2-yl)benzo[c][1,2,5] thiadiazol-4-yl)thiophen-2-yl)-9,9-spirobifluorene) (spiro-TBT). Through a comprehensive sub-12 femtosecond-nanosecond spectroscopic study, we demonstrate that extremely efficient and fast energy transfer occurs from the photoexcited spiro-TBT to the PCPDTBT, and ultrafast charge injection happens when the system is interfaced with ZnO as a prototypal electron-acceptor compound. The visible photosensitization can be effectively exploited and gives panchromatic photoresponse in prototype polymer/oxide bilayer photovoltaic diodes. This concept can be successfully adopted for tuning and optimizing the light absorption and photoresponse in a broad range of polymeric and hybrid solar cells. © 2013 American Chemical Society.